Fas2-ELISA in the detection of human infection by Fasciola hepatica - Espinoza J.R. (2005)
We thank Professor Santiago Mas Coma for suggestions to improve this contribution. This work was supported by grants to JRE from CONCYTEC (Consejo Nacional de Ciencia y Tecnolog?´a-PERU), Proyecto VIGIA-USAID 2003, The International Foundation for Science contract B/2856-1, Sweden and INCAGRO-PERU /Contract 007-2003.